CHANGE IN THE DURATION OF AUTOCLAVE STEAMING REGIMES OF NONFROZEN PRISMS AT DISPATCHING INTERVENTIONS IN THE PRODUCTION OF VENEER (Innovation in Woodworking Industry and Engineering design, 2026)
An approach for computing and research of the duration of regimes for autoclave steaming of non-frozen wooden prisms at limited heat power of the steam generator in cases of dispatching interventions into the regimes in order to obtain a duration that is suitable for the subsequent cutting of the veneer from the heated plasticized wood has been suggested. Using own 2D unsteady model implemented in the approach, calculations of the change of the duration of regimes for plasticizing of beech prisms in an autoclave have been carried out. The variables used during the computer simulation were, as follows: initial wood temperature of 0 °C, wood moisture content of 0.6 kg·kg−1, and cross-section dimensions of the prisms 0.4 × 0.4 m; steaming autoclave with a diameter of 2. 4 m, length of 9.0 m, and loading level of 50% for the cases of lowering by the dispatcher the maximal temperature of the basic steaming regime from 130 oC to 120, 110, and 100 oC in the 3rd, 5th, and 7th hour of this regime.